Benefits and challenges of outsourcing in electrical appliances industry: Case study of Videocon- India. - raheja, vaibhav (2010)
Outsourcing as a practice is becoming common by every passing day as firms try to outsource in order to meet their corporate goals. Outsourcing provides several benefits such as lowering of costs, improved focus on core functions, access to latest innovations etc. But despite its potential benefits, many outsourcing firms fail to realise these anticipated benefits. Only the firms which are able to manage outsourcing functions and align it with the corporate strategy are able to realise the full benefits of outsourcing.